2005
DOI: 10.1111/j.1365-2265.2005.02386.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid papillary cancers: microcarcinoma and carcinoma, incidental cancers and non‐incidental cancers – are they different diseases?

Abstract: Non-incidental cancer, apart from multifocality, showed a classical progression for all prognostic factors from microcarcinoma to larger cancers. However, real incidental PC seemed to be different from non-incidental PC microcarcinoma regarding the main prognostic features. We conclude that ultrasonography is useful not only in terms of revealing the presence of cancer but also in identifying the most aggressive cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 32 publications
(39 reference statements)
7
46
3
1
Order By: Relevance
“…Their findings suggest that these lesions, even when multifocal, seem to have an indolent natural history distinct from that of larger tumours. 24,26,28,29 Both our findings and findings from these studies contradict traditional clinical practice and training, which promotes total thyroidectomy as the optimal surgical procedure for the management of all differentiated thyroid carcinomas. 30,31 Although the percentage may be less in Canada, several US studies suggest that as many as 85% of patients with papillary carcinomas undergo total thyroidectomy regardless of the size of the tumour.…”
contrasting
confidence: 53%
“…Their findings suggest that these lesions, even when multifocal, seem to have an indolent natural history distinct from that of larger tumours. 24,26,28,29 Both our findings and findings from these studies contradict traditional clinical practice and training, which promotes total thyroidectomy as the optimal surgical procedure for the management of all differentiated thyroid carcinomas. 30,31 Although the percentage may be less in Canada, several US studies suggest that as many as 85% of patients with papillary carcinomas undergo total thyroidectomy regardless of the size of the tumour.…”
contrasting
confidence: 53%
“…Microcalcifications within malignant nodules have been observed in many studies (76,(127)(128)(129)(130) and were present in 7.1-59% of patients with PTMC (76,(127)(128)(129)(130)(131). Irregular margins of the nodules have been observed in 21.5-77% of PTMC (11,127,130,133). A taller-than wider dimension and antero-posterior diameter larger than the transverse diameter of nonpalpable thyroid nodules have also been suggested as a diagnostic feature for the presence of malignancy (76,101).…”
Section: Diagnosis Of Ptmcmentioning
confidence: 97%
“…Total/near total thyroidectomy was carried out in 100% of the cases in 17 (11,12,14,15,18,24,26,27,39,46,49,52,97,104,106,117,150) out of 44 studies that reported the type of surgery (4-6, 8, 11, 12, 14-18, 20, 23-27, 30-32, 34, 38-40, 42, 45, 46, 48-50, 58, 97, 98, 104-106, 114, 117, 121, 123, 124, 143, 148, 150). Combining the results of different studies that clearly reported the extent of surgery in 9259 patients with PTMC, total/near total thyroidectomy was performed in the 72%, subtotal thyroidectomy in the 11% and lobectomy in the 17% of the cases (4-6, 8, 11, 12, 14-18, 20, 23-27, 30-32, 34, 38-40, 42, 45, 46, 48-50, 58, 97, 98, 104-106, 114, 117, 121, 123, 124, 143, 148, 150).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…It has been proposed that incidental cancer found by histological examination of goiters would hold lower potential aggressiveness than cancers detected by fine-needle aspiration considering prognostic features, such as multifocality, lymph node metastasis and extracapsular invasion (29). On the other hand, there are many reports on the aggressive behavior of papillary microcarcinomas, which evolve not only with lymphatic regional metastases, but also with blood-borne lung, bone and brain metastases (30,31).…”
Section: Thyroid Cancer Biologymentioning
confidence: 99%